10 bibliographies of 20th century Russian literature - Moody, Fred. (Ardis)
Luker, N. J. L. A selected bibliography of works by and about Alexander Kuprin (1870-1938).--Ingold, F. P. A bibliography of works by and about Innokentii Fedorovich Annenskii.--Sendich, M. Blok's "The Twelve": a bibliography of criticism (1918-1970).--Moody, C. A bibliography of works by and about N. N. Evreinov.--Darring, G. Mayakovsky: a bibliography of criticism (1912-1930).--Luker, N. J. L. A selected bibliography of works by and about Alexander Grin (1800-1932).--Meyer, P. A bibliography of works by and about Vasilii Pavlovich Aksenov.--Smith, G. S. A bibliography of Soviet publications on Russian versification, 1958-1972.--Rydel, C. A bibliography of works by and about Bella Akhmadulina.--Kline, G. L. A bibliography of the published works of Iosif Aleksandrovich Brodsky.